Preparation method of anti-carbonization all-solid waste slag-sulphoaluminate cementing material

By combining modified lead-zinc tailings powder with silicate cement-based concrete recycled fine powder, the carbonation resistance of sulphoaluminate cement is enhanced, the problem of insufficient carbonation resistance of sulphoaluminate cement hydration products is solved, and the high durability and early strength improvement of the all-solid waste slag-sulphoaluminate cementitious material are achieved.

CN120736867AActive Publication Date: 2025-10-03CCCC (INNER MONGOLIA) CONSTRUCTION & DEVELOPMENT CO LTD

Patent Information

Application Number
CN202511254162.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-04
Publication Date
2025-10-03
Estimated Expiration
2045-09-04

AI Technical Summary

Technical Problem

The hydration products of existing sulphoaluminate cement have poor carbonation resistance, which leads to strength reduction during service and affects the durability of building structures.

Method used

By modifying the lead-zinc tailings powder, anti-carbonation tailings powder is formed, and mixed with sulfoaluminate cement. Iron oxide is used to convert FeS2 into ferric sulfate, thereby increasing the bond energy of ettringite crystals. At the same time, silicate cement-based concrete recycled micropowder is added to prepare an anti-carbonation enhancer, and magnesium oxide is used to fill the pores and solidify carbon dioxide to enhance the anti-carbonation ability of the cementitious material.

Benefits of technology

The carbonization resistance of all-solid waste slag-sulphoaluminate cementitious materials is improved, strength shrinkage is prevented, service life is extended, and resource utilization of industrial solid waste is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120736867A_ABST
    Figure CN120736867A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based material preparation, and particularly discloses a preparation method of an anti-carbonization all-solid waste slag-sulphoaluminate cementing material, which comprises the following steps: (1) putting a wet material formed by lead-zinc tailing powder and water into a reaction container, sealing, and heating; and mixing the obtained product with iron powder and / or iron oxide powder and water, stirring, separating out a solid product, and heating and drying in an air atmosphere to obtain the anti-carbonization tailing powder. And (2) mixing the anti-carbonization tailing powder with sulphoaluminate cement powder, and carrying out mechanical grinding treatment to obtain the modified sulphoaluminate cement. And (3) uniformly mixing blast furnace slag powder, the modified sulphoaluminate cement, fly ash, waste gypsum powder, an alkali activator, gypsum and a water reducing agent serving as raw materials to obtain the cementing material. According to the invention, the resource utilization of industrial solid waste is realized, the carbonization resistance of the cementing material is effectively improved, and the service durability of the cementing material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based material preparation, and in particular to a method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] Traditional cement-based materials primarily use Portland cement clinker as their binder. Their preparation requires high-temperature calcination, which is energy-intensive and produces significant carbon dioxide emissions. Solid waste-based cementitious materials, derived from silicoaluminous industrial solid waste and supplemented with activators such as gypsum, are hydraulic binders that can replace traditional Portland cement clinker in concrete production. Their carbon emissions are only 5-10% of those of Portland cement. This opens a new path for green development in the cement industry, promoting its low-carbon transition and facilitating the resourceful utilization of solid waste.

[0004] However, due to the generally low gelling activity of silicoaluminate industrial solid waste, the hydration reaction starts slowly, resulting in insufficient early strength development, which limits the application of solid waste-based cementitious materials in some special circumstances. Sulphoaluminate cement is a clinker with anhydrous calcium sulfoaluminate and dicalcium silicate as its main components. It has the characteristics of early strength and high strength. Combining it with solid waste-based cementitious materials can help overcome its problem of insufficient early strength development. However, the inventors have found that because the hydration product of sulphoaluminate cement is mainly ettringite, it has poor carbonation resistance and is prone to strength shrinkage under the erosion of carbon dioxide during service, resulting in a decrease in the bearing capacity of the building structure. Therefore, this composite material still has the problem of insufficient durability. Summary of the Invention

[0005] To address the aforementioned issues, the present invention provides a method for preparing a carbonization-resistant all-solid waste slag-sulfoaluminate cementitious material. This method not only achieves resource utilization of industrial solid waste but also effectively improves the carbonization resistance of the cementitious material, thereby enhancing its service durability. Specifically, the technical solution of the present invention is as follows.

[0006] A method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material comprises the following steps: (1) The wet material formed by lead-zinc tailings powder and water is placed in a reaction vessel and sealed for heating. After the completion, the obtained product is mixed with iron powder and / or iron oxide compound powder and water and stirred. After the completion, the solid product is separated and heated and dried in an air atmosphere to obtain carbonization-resistant tailings powder.

[0007] (2) The carbonization-resistant tailings powder is mixed with sulphoaluminate cement powder and subjected to mechanical grinding to obtain modified sulphoaluminate cement.

[0008] (3) Blast furnace slag powder, the modified sulphoaluminate cement, fly ash, waste gypsum powder, alkali activator, gypsum and water reducing agent are mixed as raw materials to obtain the cementitious material.

[0009] Furthermore, in step (1), the moisture content of the wet material is 24-32%. Optionally, the fineness of the lead-zinc tailings powder is not less than 200 mesh.

[0010] Furthermore, in step (1), the temperature of the heating treatment is 50-70° C., and the time is 9-14 hours.

[0011] Furthermore, in step (1), the molar ratio of the Fe element provided by the iron powder and / or iron oxide compound powder to the S element in the lead-zinc tailings powder is 1.1-1.2:2, so as to convert the sulfuric acid formed by FeS2 in the lead-zinc tailings powder into ferric sulfate or ferrous sulfate. Optionally, the iron oxide compound includes at least one of ferric oxide, ferrous oxide, and ferrosoferric oxide.

[0012] Furthermore, in step (1), the ratio of the product to water is 1 g: 3-5 mL. Optionally, the stirring time is not less than 20 min.

[0013] Furthermore, in step (1), the drying temperature is 70-80° C. and the drying time is 1-1.5 hours.

[0014] Furthermore, in step (2), the ratio of the carbonization-resistant tailings powder to the sulphoaluminate cement powder is 1.0 part by weight: 0.45-0.52 parts by weight. Optionally, the fineness of the modified sulphoaluminate cement is not less than 300 mesh.

[0015] Furthermore, in step (3), the proportions of the components in the raw materials are: 60-75 parts by weight of blast furnace slag powder, 42-55 parts by weight of modified sulphoaluminate cement, 18-25 parts by weight of fly ash, 16-22 parts by weight of waste gypsum powder, 7-11 parts by weight of alkali activator, and 2-3.1 parts by weight of water reducer.

[0016] Furthermore, in step (3), the waste gypsum includes at least one of desulfurized gypsum, fluorinated gypsum, and phosphogypsum.

[0017] Furthermore, in step (3), the alkaline activator includes at least one of sodium hydroxide, potassium hydroxide, sodium silicate, etc.

[0018] Furthermore, in step (3), the water reducer includes at least one of: a polycarboxylic acid water reducer, a naphthalene-based water reducer, an aliphatic water reducer, a lignin sulfonate water reducer, and the like.

[0019] Furthermore, in step (3), the raw materials also include an anti-carbonation enhancer prepared by the following method: mixing silicate cement-based concrete recycled fine powder with a magnesium ion solution, then adding an alkaline solution, mixing, and then standing. After completion, the solid product is separated and calcined to obtain the anti-carbonation enhancer.

[0020] Furthermore, the ratio of the Portland cement-based recycled concrete powder to the magnesium ion solution is 1g: 2-3.5mL. Optionally, the mass fraction of the magnesium ion solution is no less than 15%. The recycled powder is obtained by crushing and grinding waste Portland cement-based construction concrete.

[0021] Furthermore, the magnesium ion solution includes at least one of a magnesium chloride solution, a magnesium sulfate solution, a magnesium nitrate solution, and the like.

[0022] Furthermore, the alkali solution is added so that the magnesium ions in the magnesium ion solution can be completely precipitated. Optionally, the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, ammonia water, etc.

[0023] Furthermore, the calcination treatment is carried out at a temperature of 560-630° C. and for a time of 2-2.5 hours.

[0024] Furthermore, the anti-carbonization enhancer is added in an amount of 14-20% of the total amount of the blast furnace slag powder, modified sulphoaluminate cement and fly ash. Optionally, the anti-carbonization enhancer has a fineness of not less than 300 mesh.

[0025] Furthermore, in step (3), the raw materials may be mixed with fibers and other components as needed to further improve the mechanical properties of the resulting cementitious material. Optionally, the fibers include at least one of basalt fibers, organic fibers, and steel fibers.

[0026] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: Although adding sulphoaluminate cement to solid waste-based cementitious materials can improve early strength, the hydration products of sulphoaluminate cement have poor carbonation resistance, which easily causes strength shrinkage during service. To this end, the present invention uses anti-carbonation tailings powder prepared from lead-zinc tailings powder as raw material to modify sulphoaluminate cement, which not only improves its carbonation resistance and alleviates the problem of strength shrinkage, but also converts the industrial solid waste of lead-zinc tailings into active gelling components for the preparation of the full solid waste slag-sulphoaluminate cementitious materials of the present invention, thereby achieving multiple utilizations of lead-zinc tailings. To this end, the present invention first performs an insulation treatment on the wet material formed by lead-zinc tailings powder and water, and converts the FeS2 therein into ferrous sulfate and sulfuric acid under the action of water and oxygen. At the same time, the sulfuric acid in this process can also acid-excite the lead-zinc tailings powder, depolymerize the inert mineral phase, and improve the gelling activity of the lead-zinc tailings powder. Then, the present invention adds iron powder and / or iron oxide powder to convert the sulfuric acid into ferrous sulfate / ferric sulfate again, and after drying in air, oxidizes the ferrous sulfate into ferric sulfate. The anti-carbonization tailings powder obtained after the above treatment is mechanically ground with sulphoaluminate cement powder, and the Fe provided by the anti-carbonization tailings powder is used in the hydration process. 3+ Partially replace the Al in the ettringite crystals of the hydration product of sulphoaluminate cement 3+ , increasing the crystal bond energy, thereby increasing the Ca 2+ The activated lead-zinc tailings powder not only serves as a cementitious material but also forms more cementitious products, thereby promoting improved early strength.

[0027] Furthermore, the present invention utilizes a carbonation-resistant enhancer prepared from recycled micropowder from Portland cement-based concrete, which not only achieves resource utilization of waste concrete but also further enhances the carbonation resistance of the sulfoaluminate cement. This is because, after calcination, the magnesium oxide and hydration product calcium hydroxide in the recycled micropowder dehydrate to form magnesium oxide and calcium oxide. Simultaneously, the other hydration products—hydrated calcium silicate and hydrated calcium aluminate—also dehydrate. When added to the all-solid waste slag-sulfoaluminate cementitious material of the present invention, the magnesium hydroxide, which forms micro-expansion after hydration of the magnesium oxide, can fill and densify the pores in the cementitious material, reducing carbon dioxide infiltration channels. Furthermore, the magnesium hydroxide formed can solidify intruding carbon dioxide in the later stages of the cementitious material's service life (Mg(OH)2 + CO2 = MgCO3 + H2O), reducing erosion of ettringite. The heat released by the calcium oxide upon contact with water during the magnesium oxide hydration process also helps accelerate the hydration reaction and promote the conversion of the magnesium oxide. At the same time, the dehydrated calcium silicate and calcium aluminate serve as nucleation sites to promote the formation of hydration products in the cementitious material, thereby enhancing the early strength development of the cementitious material. The present invention utilizes the characteristics of the recycled fine powder of Portland cement-based concrete, and after modification, not only achieves higher-value resource utilization, but also enhances the carbonation resistance of the ettringite, helping to further prevent the occurrence of strength shrinkage. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings, which constitute a part of the present invention, are used to provide further understanding of the present invention and are not intended to constitute an improper limitation of the present invention.

[0029] Figure 1 This is a rendering of the actual sample of the anti-carbonization tailings powder prepared in the following Example 1.

[0030] Figure 2 This is a compressive strength test diagram of the following Example 1.

[0031] Figure 3 This is a rendering of the actual sample of the anti-carbonization tailings powder prepared in the following Example 2.

[0032] Figure 4 This is a photo of the actual sample effect of the anti-carbonization reinforcing agent prepared in the following Example 2.

[0033] Figure 5 This is a compressive strength test diagram of the following Example 2.

[0034] Figure 6 This is a rendering of the actual sample of the anti-carbonization tailings powder prepared in the following Example 3.

[0035] Figure 7 This is a photo of the actual sample effect of the anti-carbonization reinforcing agent prepared in Example 3 below.

[0036] Figure 8 This is a compressive strength test diagram of the following Example 3. DETAILED DESCRIPTION

[0037] The present invention will be further described below with reference to specific examples. It should be understood that these examples are intended to illustrate the present invention only and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are for exemplary purposes only. The technical solutions of the present invention will now be further described with reference to specific embodiments.

[0038] Example 1: A method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material, comprising the following steps: (1) Add water to the lead-zinc tailings powder with a fineness of 300 mesh (the main component is a silicon-aluminum mineral phase, and the FeS2 content is 12.37wt.%) and stir evenly to form a wet material with a moisture content of 28%. Then place the wet material in a reaction vessel and seal it, then heat it to 55°C and keep it warm for 10 hours. After completion, add iron powder to the obtained product, and the molar ratio of the Fe element provided by it to the S element in the lead-zinc tailings powder is 1.1:2. Then add clean water in a ratio of 1g:4mL of the product to water and stir continuously for 20 minutes. After completion, filter out the solid product and keep it warm at 70°C in an air atmosphere for 1.5 hours. Stir continuously during the process, and obtain anti-carbonization tailings powder (such as Figure 1 shown).

[0039] (2) The carbonization-resistant tailings powder and sulphoaluminate cement powder are mixed in a ratio of 1.0 parts by weight to 0.5 parts by weight, and then mechanically ground and passed through a 400-mesh sieve to obtain modified sulphoaluminate cement.

[0040] (3) Weigh the following raw materials in the following proportions: 70 parts by weight of granulated blast furnace slag powder, 50 parts by weight of the modified sulphoaluminate cement of this example, 20 parts by weight of Class I fly ash, 18 parts by weight of desulfurized gypsum powder, 8.5 parts by weight of sodium hydroxide, and 2.5 parts by weight of a polycarboxylate water reducer. Pour the above raw materials into a blender and mechanically stir for 5 minutes to obtain the cementitious material.

[0041] Performance test: The anti-gelling material prepared in this embodiment was mixed with clean water at a water-cement ratio of 0.42 and stirred evenly. The resulting slurry was then poured into a mold, demoulded after hardening for 24 hours, and then cured in a curing box for 28 days. The three specimens obtained were subjected to compressive strength tests (such as Figure 2(as shown) and the average value a was calculated. Simultaneously, three other specimens were placed in a carbonization chamber for 7 days, after which their compressive strength was tested and the average value b was calculated. The ratio b / a was then used as the compressive strength loss rate. A larger value indicates a smaller strength loss due to carbonization and a stronger carbonization resistance of the cementitious material. The measured compressive strength loss rate was 92.14%.

[0042] Example 2: A method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material, comprising the following steps: (1) Add water to the lead-zinc tailings powder with a fineness of 200 mesh (the same as in Example 1) and stir evenly to form a wet material with a moisture content of 24%. Then place the wet material in a reaction vessel and seal it, then heat it to 70°C and keep it warm for 9 hours. After completion, add iron powder to the obtained product, and the molar ratio of the Fe element provided by it to the S element in the lead-zinc tailings powder is 1.1:2. Then add clean water in a ratio of 1g:3mL of the product to water and stir continuously for 25 minutes. After completion, filter out the solid product, heat and dry it at 80°C in an air atmosphere for 1 hour, stirring continuously during the process, and obtain anti-carbonization tailings powder (such as Figure 3 shown).

[0043] (2) The carbonization-resistant tailings powder and sulphoaluminate cement powder were mixed in a ratio of 1.0 parts by weight to 0.45 parts by weight, and then mechanically ground and passed through a 300-mesh sieve to obtain modified sulphoaluminate cement.

[0044] (3) Mix the 200-mesh Portland cement-based concrete recycled powder with 15% magnesium sulfate solution at a ratio of 1g:3.5mL and stir evenly. 2+ :OH - Sodium hydroxide solution was added at a molar ratio of 1:1.15, stirred and allowed to stand for 10 minutes. The solid product was then filtered out and heated to 560°C for 2.5 hours. After completion, it was cooled to room temperature and then ground and passed through a 300 mesh sieve to obtain an anti-carbonization enhancer (such as Figure 4 shown).

[0045] (4) Weigh the following raw materials in the following proportions: 60 parts by weight of granulated blast furnace slag powder, 42 parts by weight of the modified sulphoaluminate cement of this example, 18 parts by weight of Class I fly ash, 16 parts by weight of desulfurized gypsum powder, 7 parts by weight of sodium silicate, 2 parts by weight of polycarboxylate water reducer, and 16.8 parts by weight of the anti-carbonation enhancer of this example. Pour the above raw materials into a blender and mechanically stir for 5 minutes to obtain the cementitious material.

[0046] Performance test: The compressive strength of the gelling material prepared in this embodiment before and after carbonization treatment was tested using the same method as in Example 1 (e.g. Figure 5 As shown), then the compressive strength loss rate is calculated = 97.59%.

[0047] Example 3: A method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material, comprising the following steps: (1) Add water to the lead-zinc tailings powder with a fineness of 250 mesh (the same as in Example 1) and stir evenly to form a wet material with a moisture content of 32%. Then place the wet material in a reaction vessel and seal it, then heat it to 50°C and keep it warm for 14 hours. After completion, add iron oxide powder to the obtained product, and the molar ratio of the Fe element provided by it to the S element in the lead-zinc tailings powder is 1.2:2. Then add clean water in a ratio of 1g:5mL of the product to water and stir continuously for 25 minutes. After completion, filter out the solid product, heat and dry it at 75°C in an air atmosphere for 1 hour, stirring continuously during the process, and obtain anti-carbonization tailings powder (such as Figure 6 shown).

[0048] (2) The carbonization-resistant tailings powder and sulphoaluminate cement powder were mixed in a ratio of 1.0 parts by weight to 0.52 parts by weight, and then mechanically ground and passed through a 350-mesh sieve to obtain modified sulphoaluminate cement.

[0049] (3) Mix the recycled micro powder of 200 mesh silicate cement-based concrete with 25% magnesium nitrate solution at a ratio of 1g:2mL and stir evenly. 2+ :OH - Add ammonia water at a molar ratio of 1:1.1, stir and let it stand for 10 minutes. Then filter out the solid product and heat it to 630℃ for 2 hours. After completion, cool it to room temperature, grind it, and pass it through a 350 mesh sieve to obtain an anti-carbonization enhancer (such as Figure 7 shown).

[0050] (4) Weigh the following raw materials in the following proportions: 75 parts by weight of granulated blast furnace slag powder, 55 parts by weight of the modified sulphoaluminate cement of this example, 25 parts by weight of Class I fly ash, 22 parts by weight of desulfurized gypsum powder, 6 parts by weight of sodium hydroxide, 5 parts by weight of sodium silicate, 3.1 parts by weight of sodium lignin sulfonate water reducer, and 31 parts by weight of the anti-carbonation enhancer of this example. Pour the above raw materials into a blender and mechanically stir for 5 minutes to obtain the cementitious material.

[0051] Performance test: The compressive strength of the gelling material prepared in this embodiment before and after carbonization treatment was tested using the same method as in Example 1 (e.g. Figure 8 As shown), then calculate the compressive strength loss rate = 98.06%.

[0052] Example 4: A method for preparing a fully solid waste slag-sulphoaluminate cementitious material, comprising the following steps: The following raw materials were weighed in the following proportions: 70 parts by weight of granulated blast furnace slag powder, 50 parts by weight of sulphoaluminate cement, 20 parts by weight of Class I fly ash, 18 parts by weight of desulfurized gypsum powder, 8.5 parts by weight of sodium hydroxide, and 2.5 parts by weight of a polycarboxylate superplasticizer. These raw materials were placed in a blender and mechanically stirred for 5 minutes to obtain the cementitious material.

[0053] Performance test: The compressive strength of the cementitious material prepared in this embodiment before and after carbonization treatment was tested using the same method as in the above embodiment 1, and then the compressive strength loss rate was calculated to be 74.33%.

[0054] Example 5: A method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material, comprising the following steps: (1) Water was added to 300-mesh lead-zinc tailings powder (the same as in Example 1) and stirred uniformly to form a wet material with a moisture content of 28%. The wet material was then placed in a sealed reaction vessel and heated to 55°C for 10 hours. After completion, the obtained solid product was kept at 70°C in an air atmosphere for 1.5 hours with continuous stirring. After completion, carbonization-resistant tailings powder was obtained.

[0055] (2) The carbonization-resistant tailings powder and sulphoaluminate cement powder are mixed in a ratio of 1.0 parts by weight to 0.5 parts by weight, and then mechanically ground and passed through a 400-mesh sieve to obtain modified sulphoaluminate cement.

[0056] (3) Weigh the following raw materials in the following proportions: 70 parts by weight of granulated blast furnace slag powder, 50 parts by weight of the modified sulphoaluminate cement of this example, 20 parts by weight of Class I fly ash, 18 parts by weight of desulfurized gypsum powder, 8.5 parts by weight of sodium hydroxide, and 2.5 parts by weight of a polycarboxylate water reducer. Pour the above raw materials into a blender and mechanically stir for 5 minutes to obtain the cementitious material.

[0057] Performance test: The compressive strength of the cementitious material prepared in this embodiment before and after carbonization treatment was tested using the same method as in the above embodiment 1, and then the compressive strength loss rate was calculated to be 86.72%.

[0058] Example 6: A method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material, comprising the following steps: (1) Lead-zinc tailings powder with a fineness of 300 mesh (the same as in Example 1) and sulphoaluminate cement powder were mixed in a ratio of 1.0 part by weight: 0.5 part by weight, and then mechanically ground and passed through a 400-mesh sieve to obtain modified sulphoaluminate cement.

[0059] (2) Weigh the following raw materials in the following proportions: 70 parts by weight of granulated blast furnace slag powder, 50 parts by weight of the modified sulphoaluminate cement of this example, 20 parts by weight of Class I fly ash, 18 parts by weight of desulfurized gypsum powder, 8.5 parts by weight of sodium hydroxide, and 2.5 parts by weight of a polycarboxylate water reducer. Pour the above raw materials into a blender and mechanically stir for 5 minutes to obtain the cementitious material.

[0060] Performance test: The compressive strength of the cementitious material prepared in this embodiment before and after carbonization treatment was tested using the same method as in the above embodiment 1, and then the compressive strength loss rate was calculated to be 79.42%.

[0061] Example 7: A method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material, comprising the following steps: (1) Mix the recycled micro powder of 200 mesh silicate cement-based concrete with 15% magnesium sulfate solution at a ratio of 1g:3.5mL and stir evenly. 2+ :OH - Sodium hydroxide solution was added at a molar ratio of 1:1.15, stirred and allowed to stand for 10 minutes, and then the solid product was filtered out, dried, ground, and passed through a 300-mesh sieve to obtain an anti-carbonization enhancer.

[0062] (2) Weigh the following raw materials in the following proportions: 60 parts by weight of granulated blast furnace slag powder, 42 parts by weight of the modified sulphoaluminate cement of Example 2, 18 parts by weight of Class I fly ash, 16 parts by weight of desulfurized gypsum powder, 7 parts by weight of sodium silicate, 2 parts by weight of a polycarboxylate water reducer, and 16.8 parts by weight of the anti-carbonation enhancer of this example. Pour the above raw materials into a blender and mechanically stir for 5 minutes to obtain the cementitious material.

[0063] Performance test: The compressive strength of the cementitious material prepared in this embodiment before and after carbonization treatment was tested using the same method as in the above embodiment 1, and then the compressive strength loss rate was calculated to be 93.68%.

[0064] Example 8: A method for preparing a carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material, comprising the following steps: (1) Grind the recycled micropowder of silicate cement-based concrete and pass it through a 350-mesh sieve to obtain an anti-carbonation enhancer.

[0065] (2) Weigh the following raw materials in the following proportions: 75 parts by weight of granulated blast furnace slag powder, 55 parts by weight of the modified sulfoaluminate cement of Example 3, 25 parts by weight of Class I fly ash, 22 parts by weight of desulfurized gypsum powder, 6 parts by weight of sodium hydroxide, 5 parts by weight of sodium silicate, 3.1 parts by weight of sodium lignin sulfonate water reducer, and 31 parts by weight of the anti-carbonation enhancer of this example. Pour the above raw materials into a blender and mechanically stir for 5 minutes to obtain the cementitious material.

[0066] Performance test: The compressive strength of the cementitious material prepared in this embodiment before and after carbonization treatment was tested using the same method as in the above embodiment 1, and then the compressive strength loss rate was calculated to be 92.76%.

[0067] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art will appreciate that they may modify the technical solutions described in the foregoing embodiments or substitute equivalents for some of the technical features. Any such modifications, equivalent substitutions, and improvements shall be within the scope of protection of the present invention.

Claims

1. A method for preparing carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material, characterized in that: The steps include: (1) placing a wet material formed by lead-zinc tailings powder and water in a reaction vessel and sealing it for heating treatment; after the completion, mixing the obtained product with iron powder and / or iron oxide compound powder and water and stirring the mixture; after the completion, separating the solid product and heating and drying it in an air atmosphere to obtain carbonization-resistant tailings powder; (2) mixing the carbonization-resistant tailings powder with sulphoaluminate cement powder and subjecting the mixture to mechanical grinding to obtain modified sulphoaluminate cement; (3) Blast furnace slag powder, the modified sulphoaluminate cement, fly ash, waste gypsum powder, alkali activator, gypsum and water reducing agent are mixed as raw materials to obtain the cementitious material.

2. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to claim 1, characterized in that: In step (1), the moisture content of the wet material is 24-32%; Alternatively, in step (1), the fineness of the lead-zinc tailings powder is not less than 200 mesh; Alternatively, in step (1), the heating treatment temperature is 50-70° C. and the time is 9-14 hours.

3. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to claim 1, characterized in that: In step (1), the molar ratio of the Fe element provided by the iron powder and / or iron oxide compound powder to the S element in the lead-zinc tailings powder is 1.1-1.2:2; Alternatively, in step (1), the iron oxide compound comprises at least one of ferric oxide, ferrous oxide, and ferrosoferric oxide; Alternatively, in step (1), the ratio of the product to water is 1 g: 3-5 mL; Alternatively, in step (1), the stirring time is not less than 20 minutes; Alternatively, in step (1), the drying temperature is 70-80° C. and the drying time is 1-1.5 hours.

4. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to claim 1, characterized in that: In step (2), the ratio of the carbonization-resistant tailings powder to the sulphoaluminate cement powder is 1.0 part by weight: 0.45 to 0.52 parts by weight; or, in step (2), the fineness of the modified sulphoaluminate cement is not less than 300 mesh.

5. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to claim 1, characterized in that: In step (3), the proportions of the components in the raw materials are: 60-75 parts by weight of blast furnace slag powder, 42-55 parts by weight of modified sulphoaluminate cement, 18-25 parts by weight of fly ash, 16-22 parts by weight of waste gypsum powder, 7-11 parts by weight of alkali activator, and 2-3.1 parts by weight of water reducer.

6. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to claim 1, characterized in that: In step (3), the waste gypsum includes at least one of desulfurized gypsum, fluorinated gypsum, and phosphogypsum; Alternatively, in step (3), the alkaline activator comprises: at least one of sodium hydroxide, potassium hydroxide, and sodium silicate; Alternatively, in step (3), the water reducer includes at least one of a polycarboxylic acid water reducer, a naphthalene-based water reducer, an aliphatic water reducer, and a lignin sulfonate water reducer.

7. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to any one of claims 1 to 6, characterized in that: In step (3), the raw materials also include an anti-carbonation enhancer prepared by the following method: mixing silicate cement-based concrete recycled micropowder with a magnesium ion solution, then adding an alkali solution, mixing, and then standing; after completion, separating the solid product and calcining it to obtain the anti-carbonation enhancer.

8. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to claim 7, characterized in that: The ratio of the silicate cement-based concrete recycled fine powder to the magnesium ion solution is 1 g: 2-3.5 mL; or the mass fraction of the magnesium ion solution is not less than 15%.

9. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to claim 7, characterized in that: The magnesium ion solution includes at least one of a magnesium chloride solution, a magnesium sulfate solution, and a magnesium nitrate solution; Alternatively, the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, and ammonia solution; Alternatively, the calcination treatment is carried out at a temperature of 560-630° C. and for a time of 2-2.5 hours.

10. The method for preparing the carbonization-resistant all-solid waste slag-sulphoaluminate cementitious material according to claim 7, characterized in that: The addition ratio of the anti-carbonization enhancer is 14-20% of the total amount of the blast furnace slag powder, modified sulphoaluminate cement and fly ash; or the fineness of the anti-carbonization enhancer is not less than 300 mesh.

Citation Information

Patent Citations

  • Solid-waste-based high-iron sulphoaluminate maritime work cementing material as well as preparation method and application thereof

    CN113698117A

  • Preparation method and application of steel slag airport concrete

    CN117623717A

  • Preparation method of early-strength anti-carbonization super-sulfate cement-based material

    CN119038937A

  • Anti-carbonization low-carbon slag powder cement material and application thereof

    CN120441277A

  • Cement admixture and cement composition

    JP2004051423A

Cited By

  • Quick-curing high-viscosity high-strength road cold patch material and preparation method thereof

    CN121318334A

  • Method for preparing alkali-activated concrete from modified sulfur-containing copper tailings

    CN122325206A